Efficient, Secure Green: Digital Utopianism and the Challenge of Making the Electrical Grid "Smart". - Slayton, Rebecca (Information & Culture, 2013)
Electrical grids have long depended upon information infrastructures--systems for exchanging information about electricity generation, transmission, distribution, and use. But only in the last decade has the notion of a "smart grid" captured the imagination of policymakers, business leaders, and technologists. Smart grid promoters promise that information technology will simultaneously improve the efficiency, reliability, and security of the grid. This article shows how these goals have come into tension as the grid's information infrastructure has shaped, and been shaped by, government policies. It advances a three-part argument. First, digital technology and digital utopianism played a significant and underanalyzed role in restructuring the electricity industry during the 1980s and 1990s. Second, industry restructuring encouraged utilities to deploy information technology in ways that sacrificed reliability, security, and even physical efficiency for economic efficiency. Third, aligning the many goals for a smart grid will require heterogeneous engineering--designing sociopolitical and technological worlds together.